A graph-based analysis for generating geographical context from a historical cadastre in Spain (17th and 18th centuries). Issue 4 (2nd October 2019) - Zaragozí, Benito; Giménez-Font, Pablo; Belda-Antolí, Antonio; Ramón-Morte, Alfredo
Abstract: The cabreves are notarial documents prepared between the 13th and 19th centuries in the Catalan and Valencian regions of Spain. These historical records were published before the first cadastral maps and contain geographical information that could help spatially reconstruct historical landscapes. However, these documents have not been used to their full potential mainly because of their semi-structured and complex nature. In this article, we propose a new graph-based interactive methodology for partially reconstructing historical landscapes. We have successfully applied this methodology for reconstructing the historical landscape of the Barony of Sella in the 18th century and the methodology has also helped us locate "El Poblet, " a previously unknown archeological site abandoned after the expulsion of the Moriscos in 1609.